NECROTIC MYELITIS OR SPINAL NECROSIS - NIETO, DIONISIO; ESCOBAR, ALFONSO I (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1949)
A case is descr
BOL INST ESTUD MED BIOL
Keywords: NECROTIZING, MYELITIS, SPINAL, NECROSIS; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA